2019 ESC/EAS Guidelines for management of dyslipidaemia: strengths and limitations. Issue 4 (11th July 2020) - Zeitouni, Michel; Sabouret, Pierre; Kerneis, Mathieu; Silvain, Johanne; Collet, Jean-Philippe; Bruckert, Eric; Montalescot, Gilles
Abstract: In 2019, the European Society of Cardiology and European Atherosclerosis Society released a new guideline document with substantial changes regarding the assessment of cardiovascular risk and treatments. The update of high-risk criteria and categories led to a better detection and primary prevention of patients at risk of a first cardiovascular event. Nonetheless, additional efforts are needed for a better inclusion of risk modifiers, especially specific to women, to improve risk stratification and direct primary prevention. Eventually, we discuss how these new guidelines implement PCSK9 inhibitors for very high-risk individuals and the evidence supporting new low-density lipoprotein cholesterol goals below, such as 55 and 40 mg/dL.